Physiological and biochemical responses of Melissa officinalis L. to nickel stress and the protective role of salicylic acid. Issue 3 (23rd February 2017) - Soltani Maivan, Elahe; Radjabian, Tayebeh; Abrishamchi, Parvaneh; Talei, Daryush
ABSTRACT: The present study investigated the mediatory effects of salicylic acid (SA) in alleviating nickel (Ni) toxicity in Melissa officinalis L. One-month-old plants were exposed to different levels of Ni and SA concentrations in sand culture under greenhouse conditions. Excess Ni significantly inhibited the growth indices and dramatically increased accumulation of Ni in the leaves and roots. Exogenously SA applications (1.0 mM) led to a substantial improvement in the shoot and root fresh and dry weights. Foliar application of SA mitigated the deleterious effects of Ni and decreased its transport to the shoots. The results showed a significant loss in chlorophylls and carotenoids contents only at 500 µM of Ni. The impact of SA was not significant in terms of chlorophyll contents, while carotenoid contents of the Ni-stressed plants were significantly affected by SA. Exposure to Ni did not modify proline accumulation. Hydrogen peroxide accumulation was observed under Ni stress, while lipid peroxidation significantly decreased at the same conditions. Application of SA caused a significant decrease in electrolyte leakage of Ni-stressed plants. Due to the high potential for Ni accumulation in the roots and translocation factor values lower than 1, M. officinalis could be introduced as an excluder medicinal plant.